Students’ Stories of Speaking English in EFL classes: A Narrative Inquiry into Factors Affecting Their Willingness to Speak - Banunaek, Johan Ariel Suwito; Siwa, Yohanis Nurak; Toni, Elvis Albertus Bin (General English Education, 2026)
Although research on factors affecting students’ willingness to speak has been extensively carried out, most studies focus more on employing quantitative research methods by identifying the influencing factors through surveys or questionnaires. Moreover, research focusing on this issue within the Indonesian contexts is scarce. Hence, this study employed a narrative inquiry to elicit participants’ lived experiences with in-depth interviews to explore how four EFL students experience and reflect on the factors influencing them to speak in their EFL classes. The findings revealed that there are five internal factors affecting students’ willingness to speak, they are language anxiety, fear of negative evaluation, confidence, motivation, and self-directed learning. Moreover, peer influence, teacher feedback practices, and classroom activities become external factors affecting students’ willingness to speak. And students’ reflect their speaking experiences as identity and recognition, narratives of change from elementary and junior high school to senior high school, and agency.